Assessing the safety and efficacy of TAVR compared to SAVR in low-to-intermediate surgical risk patients with aortic valve stenosis: An overview of reviews. (1st September 2020) - Mc Morrow, Roisin; Kriza, Christine; Urbán, Patricia; Amenta, Valeria; Amaro, Juan Antonio Blasco; Panidis, Dimitris; Chassaigne, Hubert; Griesinger, Claudius Benedict
Abstract: Background: Transcatheter aortic valve replacement (TAVR) was initially introduced to treat patients with aortic valve stenosis (AS) at high-risk for surgical aortic valve replacement (SAVR). Today, there is ample evidence supporting TAVR in high-risk groups. However, in recent years TAVR has been extended to low-to intermediate risk groups and relevant clinical evidence is still emerging, leaving some uncertainties. Methods: To obtain information on TAVR versus SAVR in low-to intermediate risk groups, we conducted an overview of systematic reviews following PRISMA guidelines and based on a systematic search of EMBASE, MEDLINE, Cochrane and CRD databases. We focused on systematic reviews assessing mortality and VARC 2 as clinical outcomes. Results: The majority of the 11 systematic reviews included in our study reported no differences in mortality between TAVR and SAVR at short and long-term follow-up times. Two reviews that included the most recent RCTs on low-risk patients reported a decreased mortality risk with TAVR at one-year follow-up. Regarding the secondary endpoints of stroke and MI, the majority of studies presented similar results for TAVR and SAVR. Acute Kidney Injury, Bleeding Complications, Atrial Fibrillation were less frequent with TAVR, with lower risk of Permanent Pacemaker Implantation and Aortic Regurgitation with SAVR. Conclusions: Our overview indicated that TAVR is a promising intervention for low-to-intermediate surgical risk patients; however additional evidence from longer term follow-up is needed to confirm these findings. This overview highlights inconsistencies about reporting and presentation of data, most notably limited clarity on effects of risk of bias on trial results. Highlights: We reviewed the evidence for TAVR and SAVR in low-to intermediate risk patients. Most reviews found no difference in mortality between TAVR and SAVR. Acute Kidney Injury, Bleeding and Atrial Fibrillation were less frequent with TAVR. Pacemaker Implantation and Aortic Regurgitation were less frequent with SAVR. Most reviews found no difference for Stroke and Myocardial Infarction.